Culture clash - "Gabriel, Mark" ("600 Rinehart Road, Lake Mary :")
Includes bibliography and index
Keywords: "ISLAM - CONTROVERSIAL LITERATURE;ISLAM - DOCTRINES;ISLAM AND POLITICS;CIVILIZATION, ISLAMIC;WOMEN IN ISLAM;WOMEN'S RIGHTS - RELIGIOUS ASPECTS - ISLAM;ISLAMIC COUNTRIES - RELATIONS - UNITED STATES;UNITED STATES - RELATIONS - ISLAMIC COUNTRIES"